2009
DOI: 10.1016/j.vetimm.2008.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Course of infection and immune responses in the respiratory tract of IBV infected broilers after superinfection with E. coli

Abstract: Colibacillosis results from infection with avian pathogenic Escherichia coli bacteria. Healthy broilers are resistant to inhaled E. coli, but previous infection with vaccine or virulent strains of Infectious Bronchitis Virus (IBV) predisposes birds for severe colibacillosis. The aim of this study was to investigate how IBV affects the course of events upon infection with E. coli. Broilers were inoculated with IBV H120 vaccine virus or virulent M41 and challenged 5 days later with E. coli 506. A PBS and E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 27 publications
4
38
0
4
Order By: Relevance
“…It appears that from the three compartments of the respiratory tract: trachea, lungs (bronchi and parabronchi) and the airsacs, the airsacs are the only site which may harbour both IBV and E. coli during a maximum of 2 dpi. A plausible explanation for the longer persistence of airsac lesions compared to trachea and lungs upon successive infection of broilers with both IBV and E. coli was given previously by Matthijs et al (Matthijs et al, 2008), who demonstrated the occurrence of a reduction in the number of macrophages a week after inoculation with E. coli, whereas these cells were still present in high numbers at this stage in the airsacs of IBV-E. coli infected broilers. Possibly, upon the influence of both pathogens the high concentrations of macrophages will be prompted to overproduce pro-inflammatory cytokines, favouring the occurrence of the persistent airsacculitis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It appears that from the three compartments of the respiratory tract: trachea, lungs (bronchi and parabronchi) and the airsacs, the airsacs are the only site which may harbour both IBV and E. coli during a maximum of 2 dpi. A plausible explanation for the longer persistence of airsac lesions compared to trachea and lungs upon successive infection of broilers with both IBV and E. coli was given previously by Matthijs et al (Matthijs et al, 2008), who demonstrated the occurrence of a reduction in the number of macrophages a week after inoculation with E. coli, whereas these cells were still present in high numbers at this stage in the airsacs of IBV-E. coli infected broilers. Possibly, upon the influence of both pathogens the high concentrations of macrophages will be prompted to overproduce pro-inflammatory cytokines, favouring the occurrence of the persistent airsacculitis.…”
Section: Discussionmentioning
confidence: 85%
“…From 2 to 5 days following IBV inoculation the number of birds with nasal discharge in the M41 group was significantly higher in comparison with the H120 group (for detailed information see Matthijs et al, 2008).…”
Section: Nasal Dischargementioning
confidence: 99%
“…Slides were washed in PBS and incubated for 1 h with optimally diluted primary Ab or isotype controls (Table I) in staining buffer. Sections were washed three times and blocked with normal horse serum diluted in PBS followed by incubation with biotinylated horse anti-mouse IgG and avidinbiotinylated enzyme complex (VECTASTAIN Elite) as described previously (27). Color development was done using 3,3-diaminobenzidine tetrahydrochloride (Sigma-Aldrich).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…However, the tracheal mucosa is highly responsive to infection and reacts with extensive lymphocyte infiltration followed by proliferation (Gaunson et al 2000;Gaunson et al 2006;Matthijs et al 2009). Tracheal lesions characteristic for Mycoplasma infections predominantly consist of proliferating B cells (Gaunson et al 2006) and this is similar to IBV infection (Kotani et al 2000).…”
Section: Humoral Immune Responses In the Rtmentioning
confidence: 99%